2013
DOI: 10.1111/j.1463-1318.2012.03179.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing circumferential resection margin in rectal cancer

Abstract: Aim  Abdominoperineal excision (APR) has been associated with higher circumferential resection margin (CRM) involvement and local recurrence rates than extralevator APR for low rectal cancer. This study aimed to evaluate the CRMs in APR and low anterior resection (LAR) specimens and to identify factors influencing CRM involvement. Method  All pathological specimens from consecutive patients with rectal cancer who underwent curative resection at the Cleveland Clinic Florida, from January 2000 to July 2010, were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 28 publications
1
22
0
1
Order By: Relevance
“…In recent reports from specialized centers, the risk of CRM involvement after modern APE procedures was around 14%. 2,12 Also, in a recent single-center retrospective study with comparable study populations, no oncological advantages were found with ELAPE compared with conventional APE. 7 Positive CRM was found in 17% after ELAPE and 20% after conventional APE.…”
Section: Discussionmentioning
confidence: 93%
“…In recent reports from specialized centers, the risk of CRM involvement after modern APE procedures was around 14%. 2,12 Also, in a recent single-center retrospective study with comparable study populations, no oncological advantages were found with ELAPE compared with conventional APE. 7 Positive CRM was found in 17% after ELAPE and 20% after conventional APE.…”
Section: Discussionmentioning
confidence: 93%
“…19,22,29 It is usually higher in low rectal cancer, as compared with high rectal tumors. 14,30 The reasons are the special anatomy of the lower rectum and the suboptimal surgical technique. The low rectum is characterized by a decreased mesorectal volume with less extrarectal tissue around the rectal tumor, 15 inducing a shorter CRM in term of millimeters 5 and subsequently an increased risk of positive CRM.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to poor TME quality, a significant association of positive CRM with low tumors has been demonstrated [40,42].…”
Section: Oncological Outcome and Efficiencymentioning
confidence: 84%
“…Especially in circumferential resection margin(CRM)-negative patients, substantial damage to the mesorectal specimen is a main risk factor for local recurrence [41]. Poor quality of mesorectal resection has been shown to be associated with low rectal tumors [40,42].…”
Section: Quality Of Mesorectal Excisionmentioning
confidence: 99%